Investigation on mechanical properties of AA2024/HBN composites prepared by stir casting method. (2021) - Rajkumar, S.; Arulmurugan, B.; Teklemariam, Aklilu; Tafesse, Dawit; Mekonnen, Addisalem; Mulugeta, Lijalem
Abstract: The present study was used to improve the material properties such as tensile strength (UTS) and hardness (HV). hard boron nitride (HBN) reinforced AA2024 aluminum matrix composites (AMCs) was created through the stir casting process. The impact of different weight percentages of HBN (0%, 5%, 10%, 15%, 20%) filler on the mechanical properties of AMCs has been investigated. According to ASTM specifications, the hardness, tensile strength, and compression strength of HBN filled, and unfilled base AA2024 alloy composites was measured. The results show that HBN filled AA2024 alloy strengthened HBN composites had improved mechanical properties than unfilled AA2024 base alloy.